(untitled) (Global Journal of Science Frontier Research, 2022)
The article answers the question about the cause of the expansion of the Earth The direct cause of the expansion of the Earth is the increase of basalt magma in the mantle of the globe and oceanic plates The final answer is short but it still requires the basic processes and laws of nature to be taken into account Such a basic issue is explaining the issue of the existence of a heat source in the middle of the Earth and the processes of ionization and recombination of matter The author argues with the view of the generally accepted theory of lithospheric plate tectonics that there is basically no heat source and the existing endogenous heat of the Earth is relict heat It is also under dispute that the cause of geological activity is the drift of lithospheric plates According to the theory of the primal forces of nature the source of endogenous heat is a thermonuclear reactor in the core of the Earth analogous to a reactor operating in the core of the sun The peculiarity of the expansion phenomenon is the process of hot plasma recombination The phenomenon of the expansion of the Earth is related to ionization processes and reactions of the synthesis of ionized particles of matter Basalt magma is created in the process of recombination of hot plasma matter with an ionic structure and very high density The forming basalt magma is a matter with an atomic structure and a density much lower than that of plasma When an electron is placed in orbit the particle diameter increases one hundred thousand times When the plasma pressure exceeds the sealing forces of the reaction chamber plasma bursts into the D zone 2 750 - 2 900 km outside the Earth s core The phenomenon is analogous to solar prominences A small volume of plasma ejected with an ionic structure corresponds to a huge volume of basalt with an atomic structure As a result the spurt of a small amount of plasma causes a significant increase in the volume of magmatic matter in the center of the globe Since the electrons involved in the transformation have a low mass it can be said that the transformation of plasma into basalt magma occurs without changing the mass The expansion of the Earth manifested by a tenfold increase in the volume of the globe is a phenomenon that appeared 500 million years ago The new matter is only basalt magma oceanite The processes of matter transformation and the action of electromagnetic forces that cause the uplift of the Earth s mantle and the formation of rifts are explained An important element of the expansion phenomenon is the role of hydrogen which accounts for over 90 of the magma formed Under deep conditions in hot magma hydrogen initially occurs as a component of the magma alloy and causes the primary expansion effect At a lower temperature 400-600 C hydrogen is released from the magma as a gas and reacts with elemental carbon to form methane and with carbon monoxide to form methane and water In this way the total water resources on the globe and natural gas resources are increasing The excess hydrogen gas migrates to the atmosphere and accumulates in the exoster The cause-and-effect analysis of geological phenomena confirms the thesis about ion synthesis reactions in the Earth s core and the process of hot plasma recombination So the source of heat is the core of the Earth and its energy potential tends to increase You can also refer to geothermal energy as natural nuclear energy The explanation of the phenomenon of expansion and the nature of the Earth s endogenous heat source leads to the conclusion about the use of geothermal energy in planning energy and climate policy Understanding the nature of geological processes clearly indicates the continuity of climate warming and an increase in geological activity An optimistic conclusion is the prospect of using geothermal energy In light of this conclusion the concept of a 10 km deep heat pump a deep-sea CHP plant with a capacity of 30-40 MW becomes particularly interesting The guarantee of obtaining a positive effect in every place and neutrality for the environment will be strong arguments of the implementation offer